Validation of the Ukrainian version of the Parental Burnout Assessment - Zbrodska, Iryna; Roskam, Isabelle; Dolynska, Lubov; Mikolajczak, Moïra (Frontiers in Psychology, 2022)
The aim of the present study was to develop a Ukrainian version of the Parental Burnout Assessment (PBA) and examine its psychometric properties among Ukrainian parents. We examined the factorial structure of the Ukrainian version of the PBA (PBA-UA) and its relation with other variables, both antecedents and consequences of PB, in a sample of 1896 parents including 1735 (91,5%) mothers and 161 (8,5%) fathers. The original four-factor model (exhaustion from parental role, emotional distancing from one’s child, feelings of being fed up with parenting and contrast with previous parental self) and second-order model with a global parental burnout as a second-order factor fit the data well. The results of both subscale and global scores were reliable. The PBA-UA showed a positive association with perfectionism and general stress and a negative association with resilience. The low association with socio-demographic factors (i.e., marital status, number of children, number of children living in the household, work status) was replicated in accordance with previous studies of parental burnout, nevertheless mothers had higher level of parental burnout than fathers. PBA-UA also predicted both parental neglect and parental violence, even beyond general stress. The good psychometric properties of the PBA-UA suggests that this questionnaire can be used to assess parental burnout among Ukrainian parents.